Colombia : Technical Assistance Report-Financial Soundness Indicators Mission. (IMF Staff Country Reports; Country Report ;, 2022)
The Statistics Department (STA) of the International Monetary Fund (IMF) provided technical assistance (TA) on financial soundness indicators (FSI) to Superintendencia Financiera de Colombia (SFC) during August 30-September 3, 2021. The TA mission took place at the request of and with the support of the IMF's Western Hemisphere Department (WHD). Due to travel restrictions because of the COVID-19 pandemic, the mission was conducted remotely via video conferences. The mission assisted the SFC officials to (i) review the characteristics of financial institutions and ensure proper classification of financial institutions as deposit-takers (DTs) or other financial corporations (OFCs) for the compilation of FSIs as set out in the IMF's 2019 Financial Soundness Indicators Compilation Guide (2019 FSIs Guide); and (ii) develop a work program and timeline to revise the reported FSIs because of the mission's work.